L'estuaire de la Charente de la Protohistoire au Moyen Âge La Challonnière et Mortantambe (Charente-Maritime) - Laporte, Luc (Documents d'archéologie française, 1998)
The studies compiled here all pertain to the same area, located between the Charente river valley and the Saintonge marshlands, a perpetually shifting and inhospitable setting that constitutes a privileged held of study for grasping the numerous and complex interactions between the human populations and their natural environment A seaside site and a plains site were excavated at the time of a motorway construction protect (the A 837 between Saintes and Rochefort), and the vestiges found illustrate the diversity of settlement and uses of these lands. In La Challonnière a saltworks (4th-3rd century BC) was uncovered and its activities retraced m detail, as well as an early Middle Ages settlement and its ceramic artefacts typical of Saintonge workshops. In Mortantambe a small rural homestead (2nd-7st century BO was examined along with the evidence of its economy (farming, hunting fishing metal working. J. and structures and graves attesting occupation from the 8th to the 9th century In parallel, the progression of the filling-in of the estuary was retraced by means of multidisciplinary analysis of deep sondages These studies make a fundamental contribution to the history of the settlement and the countryside in the Rochefort hinterland.